Une famille transatlantique : les Fleuriau - Jacques de Cauna (Les Cahiers de Framespa)
The character of Aimé-Benjamin Fleuriau, plantation owner on the island of Saint-Domingue, born of a protestant family of La Rochelle, France, has become a true legend in his native town since a Ph.D. dissertation was devoted to him in 1982.It is, however, the issue of racial mixing [métissage], through one of the Domingan sons of his « housekeeper » [ménagère], which has recently inspired a novel rewarded with the Prix Renaudot, and then his whole « colored » family which has just been the object of a new Ph.D. at the university of Michigan. We can clearly see today, through the new context of cultural studies, how French families dealt with colonial contingencies characterized in particular by the presence of Blacks and free men of color in La Rochelle (he brought back with him two of his daughters of color and gave plantations and slaves to his sons of color who stayed back in Saint-Domingue) with an undeniable flexibility in the adaptation of their traditional strategies regarding kinship, marriage, godparents, and inheritance.The family of La Rochelle is in a way remodelled in the light of the Domingan slave society, but still seeking to preserve the interests of its members. The issue is to establish, at first, that colonial trade in general has marked and shaped France itself as much as it did its colonies. Then, conversely, through a wide choice of archival and iconographic sources, that the family relationships, on affective and private grounds, modelled transatlantic exchanges and the relationships between blacks and whites. The notional categories of races, gender, and religion are thus revisited by an analysis – both historiographic and cultural – which not only takes us to La Rochelle and Saint-Domingue but also, after a strange turn of events, to Africa, in the direct line of the colonial and maritime tradition preserved by the descendents.